Training On The Utilization Of Natural Potential As An Innovation Program Waleran Village Tuban - Ngainin, Nurul; M, Rr.Kusuma Dwi N.; M, Ahmad Shobba Hilalul; Septiawan , Firman (PUDAK: Local Wisdom Community Journal, 2024)
Corn is one of the most important carbohydrate-producing food crops in the world, apart from wheat and rice. Waleran Village has natural potential in the form of abundant corn. The corn harvest is only sold in wet and dry form, and there is no processing to become a new product or an additional product. This is due to a lack of knowledge regarding skills in processing corn as a crop. Apart from that, most people in Waleran village work as corn farmers, so there is a need for product innovation to utilize the natural potential of Waleran village. This corn processing activity aims to provide skills training in processing corn into contemporary, healthy products with high selling value. This training took place at MI Al-Ikhlas, Waleran village, Tuban. This activity involved PKK mothers, village heads, and ordinary people in Waleran village. This service approach uses a Community Development model approach. This approach involves the community directly as the subject and object of implementing community service activities. The method used is by offering skills training in processing corn into products that have sales value (sticks & brownies) and then implementing and evaluating knowledge regarding how to process the harvested corn. The results of this activity produce people who have the knowledge and skills to utilize the corn harvest into a product with high selling value, by processing corn into products in the form of corn sticks and corn brownies.